2023
DOI: 10.3390/vaccines11091490
|View full text |Cite
|
Sign up to set email alerts
|

HPV Vaccination in Immunosuppressed Patients with Established Skin Warts and Non-Melanoma Skin Cancer: A Single-Institutional Cohort Study

Simon Bossart,
Cloé Daneluzzi,
Matthias B. Moor
et al.

Abstract: cSCC (cutaneous squamous cell carcinoma) and its precursors are a major cause of morbidity, especially in immunosuppressed patients, and are frequently associated with human papillomavirus (HPV) infections. The purpose of this study is to investigate the therapeutic potential of alpha-HPV vaccination for immunosuppressed patients with established cSCC and its precursors. In this retrospective study, all patients who received Gardasil-9®, a nonavalent HPV vaccine, as secondary prophylaxis were examined. Dermato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…The proximal nail matrix expresses lower levels of HLA-A/B/C, has fewer CD4+ and CD8+ T cells, and the antigen-presenting capacity of Table 1. Risk stratification of HPV type High-risk 16,18,31,33,35,39,45,51,52,56,58,59,66,11,40,42,43,44,54,61,72,81,89 Classification by carcinogenic risk of alpha HPVs [9]. Bold indicates inclusion in Gardasil-9® vaccine.…”
Section: Pathogenesismentioning
confidence: 99%
See 2 more Smart Citations
“…The proximal nail matrix expresses lower levels of HLA-A/B/C, has fewer CD4+ and CD8+ T cells, and the antigen-presenting capacity of Table 1. Risk stratification of HPV type High-risk 16,18,31,33,35,39,45,51,52,56,58,59,66,11,40,42,43,44,54,61,72,81,89 Classification by carcinogenic risk of alpha HPVs [9]. Bold indicates inclusion in Gardasil-9® vaccine.…”
Section: Pathogenesismentioning
confidence: 99%
“…Intramuscular injection with Gardasil-9 has also been shown to reduce the actinic keratosis burden in immunocompetent patients with significant actinic damage [55]. A retrospective study of immunocompromised patients with a history of cutaneous SCC and viral warts evaluated the number of dermatological procedures occurring pre-and postvaccination with Gardasil-9 [56]. Bossart et al [56] identified a reduction in the number of dermatologic interventions following vaccination with Gardsil-9.…”
Section: Standard and Emerging Treatments For Nail Unit Sccmentioning
confidence: 99%
See 1 more Smart Citation